1987
DOI: 10.1002/jnr.490170308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of purkinje cell loss on cerebellar gangliosides in nervous mutant mice

Abstract: The distribution of cerebellar gangliosides was studied in adult (73 +/- 2 days) nervous (nr/nr) mutant mice which lose 50-90% of their Purkinje cells. This neuronal loss is associated with significant reductions in cerebellar weight and ganglioside concentration. The cerebellar dry weights (mg) and the ganglioside concentrations (microgram N-acetylneuraminic acid per 100 mg dry weight) in nr/nr mice and age-matched normal littermates (+/?) are 7.4 +/- 0.3 mg and 13.2 +/- 0.4 mg; and 411.7 +/- 4.8 micrograms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The percentage composition of cerebellar gangliosides in several mutants and their normal littermates generally agreed with previously published data on these mutants (Irwin, 1982;Seyfried et al, 1982Seyfried et al, , 1984Seyfried et al, , 1987. A minor ganglioside now identified as disialosyl paragloboside, which was present in the cerebellum of normal mice and W V J W V , rlfrl, and qk/qk mutants, was undetectable in Let+, sg/sg, and pcdlpcd mutants.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The percentage composition of cerebellar gangliosides in several mutants and their normal littermates generally agreed with previously published data on these mutants (Irwin, 1982;Seyfried et al, 1982Seyfried et al, , 1984Seyfried et al, , 1987. A minor ganglioside now identified as disialosyl paragloboside, which was present in the cerebellum of normal mice and W V J W V , rlfrl, and qk/qk mutants, was undetectable in Let+, sg/sg, and pcdlpcd mutants.…”
Section: Resultssupporting
confidence: 89%
“…Previously, Seyfried et al (1982Seyfried et al ( , 1984Seyfried et al ( , 1987 have shown a 55-75% loss of G T l a in the Purkinje cell abnormality mutants. Based on this observation, it was concluded that G T l a was enriched in Purkinje cells.…”
Section: Discussionmentioning
confidence: 94%
“…LD1 is enriched in Purkinje cells and is significantly reduced in the cerebellums of the nervous and the Purkinje cell degeneration (PCD) mutant mice (Seyfried et al. 1982a,b; Seyfried et al. 1987; Chou et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although GD3 content was largely unaffected in the Hexb )/) and the b-gal )/) mice, the content of LD1 was increased in association with GM2 and GM1 storage in these mutants, respectively. LD1 is enriched in Purkinje cells and is significantly reduced in the cerebellums of the nervous and the Purkinje cell degeneration (PCD) mutant mice (Seyfried et al 1982a,b;Seyfried et al 1987;Chou et al 1990 Seyfried andYu 1990). Interestingly, these mice also express retinal degeneration and visual impairment (Mullen et al 1976;Ren et al 2000;Chang et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that postnatal GD3 staining (A) is seen in the EGL (arrows) but not the absence of staining of hrkinje cells in their study the Purbnje cell layer, and synaptophysin staining (B) is was a result of the less-sensitive imunohistochemical already Present in the 1% around the PurkinJe cell bodies, techniques used. Seyfried et [1987] have suggested and in the developing ~olecular layer. At 9 days Postnatal that ganglioside G~~~ is enriched in hrkinje cells, although no immunocytochemical evidence is yet available weak GD3 staining of Purkinje cells (C) is seen in folia in which synaptophysin staining (D) is still intense and punctate for this, which raises the possibility that the antibody in nature.…”
Section: G D~ Ganglioside and Purkinje Cellsmentioning
confidence: 99%